Pharmacological Studies of Tentacle Extract from the Jellyfish Cyanea capillata in Isolated Rat Aorta - Liming Zhang; Liang Xiao; Jiemin Zheng; Guoyan Liu; Zhi Zhang; Fei Nie; Bo Zhang; Qianqian Wang; Beilei Wang (Marine Drugs, 2013)
Our previous studies demonstrated that tentacle extract (TE) from the jellyfish, Cyanea capillata, could cause a dose-dependent increase of systolic blood pressure, which seemed to be the result of direct constriction of vascular smooth muscle (VSM). The aim of this study is to investigate whether TE could induce vasoconstriction in vitro and to explore its potential mechanism. Using isolated aorta rings, a direct contractile response of TE was verified, which showed that TE could induce concentration-dependent contractile responses in both endothelium-intact and -denuded aortas. Interestingly, the amplitude of contraction in the endothelium-denuded aorta was much stronger than that in the endothelium-intact one, implying that TE might also bring a weak functional relaxation in addition to vasoconstriction. Further drug intervention experiments indicated that the functional vasodilation might be mediated by nitric oxide, and that TE-induced vasoconstriction could be attributed to calcium influx via voltage-operated calcium channels (VOCCs) from the extracellular space, as well as sarcoplasmic reticulum (SR) Ca2+ release via the inositol 1,4,5-trisphosphate receptor (IP3R), leading to an increase in [Ca2+]c, instead of activation of the PLC/DAG/PKC pathway or the sympathetic nerve system.